Overview and Diversity of Fungi of the Genus Aspergillus Section Nigri on Maize and Small Grains - Lučev, Milica; Stepanović, Jelena; Kandić Raftery, Vesna; Čamdzija, Zoran; Obradović, Ana; Stevanović, Milan; Stanković, Slavica (Foods, 2025)
The presence of filamentous fungi with toxigenic ability from the Aspergillus genera is frequently found in maize kernels, and this can lead to decay and mycotoxin contamination of the kernels. In this study, we morphologically and molecularly characterized 45 isolates of Aspergillus section Nigri originating from maize and small grains (wheat, triticale, and spelt) in Serbia. Based on morphological traits, they were classified into two morpho groups. Representative isolates from both morpho groups were further molecularly characterized through sequencing of ITS, CaM and RPB2 genes in order to compare species composition, which could affect specific mycotoxicological risks. Morpho GroupI was molecularly identified as Aspergillus welwitschiae and morpho GroupII as Aspergillus tubingensis. Phylogenetic analysis of the CaM gene revealed that the Serbian Aspergillus welwitschiae isolate belongs to the H8 haplotype, while A. tubingensis isolates clustered into two subclusters. This is the first report of A. tubingensis as the causal agent of black mold of small grains (wheat, triticale and spelt) in Serbia. This distribution underscores the ecological preferences of species within the genus Aspergillus Section Nigri across various agricultural products. It emphasizes the importance of comprehending their occurrence, distribution, aggressiveness and potential for mycotoxin production in food safety assessments.